Immunization information systems’ implementation and characteristics across the world: a systematic review of the literature - Giacomo Pietro Vigezzi; Elena Maggioni; Laura Clavario; Lorenzo Clerico Mosina; Eleonora Raso; Corina Marjin; Andrea Parrini; Matteo Carbone; Simone Fugazza; Alberto Marchisio; Manuela Martella; Giansanto Mosconi; et al. (Expert Review of Vaccines, 2025)
Introduction Immunization Information Systems (IISs) are essential public health tools, supporting the management and analysis of vaccination data to aid clinical and strategic decision-making.Methods Following PRISMA guidelines, this systematic review investigated global state and operational characteristics of IISs. A comprehensive search across multiple databases up to 6th of June 2023, identified 2,612 articles, with 238 included.Results A significant increase in IIS research was observed in recent years, with a strong preference (84.5%) for electronic immunization registers (EIRs). Notably, 36% of IISs operate at the national level, and 47.7% meet the U.S. CDC definition, 17.0% are interoperable with personal health records, and 11.7% provide direct access to vaccination data for vaccinees or their guardians. Other key features include automated reminder systems for recipients and providers (12.1%), near real-time or real-time data entry (11.0%), the inclusion of demographic and socioeconomic data (16.7%), and the capacity to document vaccine refusal or hesitancy (10.2%).Conclusions IISs contribute to improving population-level surveillance of vaccine-preventable diseases. Persistent limitations related to data standardization, interoperability, and cost-effectiveness evaluation must be addressed. Strengthening these aspects is crucial to fully harness the potential of IISs in various healthcare settings, where enhanced vaccination tracking and targeting are most urgently needed.